The Unbiased Search of Biomarkers in Neurodegenerative Diseases - Ferrara, Pascual (Current Pharmaceutical Biotechnology, 2016)
A clear link exists between the extension of life expectancy throughout the world and the increased incidence of age-related neurodegenerative disorders. Diseases like Alzheimer’s and Parkinson’s are chronic diseases with devastating consequences for patients and their families. They also represent a major economic cost for society. Therapeutic progress has been made mainly by alleviating some of the symptoms of these diseases, but currently no cure is available. Attempts to develop new therapies have been hampered mainly because of gaps in our current knowledge about the pathogenic mechanism underlying neurodegeneration, making difficult the identification of targets for new drug development, and also because of the lack of biomarkers essential for early diagnosis, patient stratification and follow up of treatment. Taking advantage of the latest technical developments, proteomics and peptidomics based approaches are being used to identify new cellular pathophysiological pathways as well as biomarkers in biological fluids. Here we will review the results, mainly published in the last five years, of unbiased proteomics and peptidomics approaches for biomarker research using biological fluids of Alzheimer’s, Parkinson’s and Amyotrophic Lateral Sclerosis patients.
Keywords: proteomics